2021
DOI: 10.1016/j.ijantimicag.2020.106249
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in hospitalised patients in Spain: a cohort study in Madrid

Abstract: Highlights Few large series have described the clinical characteristics, treatments, costs and outcomes of COVID-19 patients in western countries. We report our experience with the first 1,255 cases who received anti-COVID-19 treatment at a Spanish hospital. The prevalence of acute respiratory distress syndrome and mortality was high in the early days of the Spanish epidemic. Older age, the presence of diabetes, cardiovascular disease, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 8 publications
4
23
3
Order By: Relevance
“…The proportion of severe to critical cases and mortality rate are known to increase in older COVID-19 patients, and men with T2DM were more likely to die. In line with other studies [32] , [35] , [42] , in the T2DM group of the present study, older age and hypertension were associated with increased risk of both hospitalization and mortality. However, male-gender was strongly linked with the risk of mortality but not with hospitalization; whereas, hypertension appeared to increase the likelihood of hospitalization but not mortality.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The proportion of severe to critical cases and mortality rate are known to increase in older COVID-19 patients, and men with T2DM were more likely to die. In line with other studies [32] , [35] , [42] , in the T2DM group of the present study, older age and hypertension were associated with increased risk of both hospitalization and mortality. However, male-gender was strongly linked with the risk of mortality but not with hospitalization; whereas, hypertension appeared to increase the likelihood of hospitalization but not mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the Non-DM group, the higher prevalence of comorbidities such as dyslipidemia, COPD/asthma, heart failure, CVD, and cancer in our T2DM group was consistent with published studies [19] , [32] , [39] , [41] . In contrast, CKD did not differ in patients with or without T2DM probably due to missing data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, 10 to 20% of hospitalized patients develop severe disease and are admitted to the ICU, of which about 40% died, during the first pandemic wave. 2,3 The vast majority of COVID-19 diagnosis is performed by detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in nasopharyngeal swabs using realtime reverse transcriptase PCR (RT-qPCR). Nevertheless, some studies have demonstrated the presence of SARS-CoV-2 RNA in other bodily fluids, including plasma, either using RT-qPCR [4][5][6] or droplet digital PCR (ddPCR).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published metaanalysis on 33 studies on COVID-19 (totaling 13,398 patients, excluding critical care-only studies), estimated that in hospitalized patients the mortality rate was 11.5% (95% CI: 7.7 -16.9%) (31). Published data from large retrospective studies on patients admitted into Spanish hospitals report death rates between 20-28% (32)(33)(34)(35)(36). It should be noted, however, that these analyses were performed on data extracted from the first epidemic wave, and APLICOV-PC was run during the second wave, which might account in differences in the availability of health resources, learning curve, and baseline severity of hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%